Acute responses to a short-format high-intensity interval session: associations with the anaerobic speed reserve in runners - Thron, M.; Ruf, L.; Buchheit, M.; Härtel, S.; Woll, A.; Altmann, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The proficiency to cope with high-intensity interval training (HIIT) is essential for many running-oriented disciplines like sprinting or middle-distance running [1]. Individualization of HIIT according to individual profiles, e.g., based on the anaerobic speed reserve (ASR), could improve training outcomes by implementing a level of external workload adjusted to the athlete`s profile [2]. A prerequisite for ASR based training prescription is the knowledge about acute reactions to high-intensity exercise. However, only few studies have addressed acute reactions to HIIT related to individual profiles and ambiguous findings in the literature exist [3, 4]. Therefore, this study aimed to compare acute responses to a short-format HIIT session between adolescent runners with higher and lower ASR. METHODS: Eighteen highly trained runners (15.83±0.86 years) underwent maximal sprinting speed (MSS) and maximal aerobic speed (MAS) assessments to determine ASR (= MSS minus MAS) and a standardized HIIT protocol (2x (20x 15s/15s @110% MAS)) was administered. Pre/post-HIIT assessments included creatine kinase (CK), neuromuscular responses (countermovement jump; CMJ; reactive strength index, RSI), heart rate recovery (HRR), and subjective measures (e.g., single item for fatigue). Pearson` r was calculated to assess relationships between pre/post differences and ASR, MSS, and MAS. RESULTS: Athletes with a lower ASR exhibited a greater increase in CK (r=-0.75; p<0.01), and decline in CMJ height and RSI (0.69=r=0.79; p<0.01) compared to athletes with a higher ASR. However, ASR and the HRR did not correlate (r=0.37; p=0.15). MAS correlated with the pre/post difference of RSI (r=-0.54, p=0.02), and MSS with the pre/post difference of CK (r=-0.50; p=0.03) and of CMJ height (r=0.76; p<0.01). Subjectively, low ASR athletes showed significant increases in fatigue and decreases in recovery variables (r=0.57; p=0.01). While MAS did not correlate with any of the subjective variables, MSS showed a positive relationship with the pre/post difference of the single item for fatigue (r=0.49; p=0.04). CONCLUSION: In summary, our findings highlight the significance of taking an athletes locomotor profile into account to understand individual tolerances to HIIT. Athletes with a higher ASR, categorized as speed types, experienced less increase in CK, less decrease in CMJ height and RSI, and less increases in subjective fatigue and recovery variables than athletes with a lower ASR, classified as endurance type. Speed types athletes might benefit from using lower proportions of their ASR during high-intensity exercise or from an advantageous muscle fiber typology to handle higher intensities with a reduced internal load [3]. These findings can help tailoring training programs to individual needs and avoid possible overload.